Anticolonialidade em São Jorge dos Ilhéus, de Jorge Amado - Mendes, Kallebe Araújo (2024)
São Jorge dos Ilhéus (2010) is a novel inspired by the peak period of development in the country's cocoa economy. Major issues affecting Ilhéus in the 1930s arise from colonial remnants that persist to the present day, such as racial, gender, and class inequalities. Jorge Amado discerns the region's contradictions and denounces them while narrating the city's history during this period from a nationalist perspective, highlighting the exploitation by foreign-capital-funded enterprises. Building upon this, the present research aims to identify anti-colonial elements in the narrative of "São Jorge dos Ilhéus" (2010), drawing from the historical trajectory of Ilhéus city, where literature, history, and sociology converge to delineate the anti-colonial characteristics in the novel under study, starting from the hypothesis that Jorge Amado serves as an interpreter of Brazil, capable of synthesizing elements of the social reality he encounters and, in a plausible manner, transplanting the major regional issues into the narrative. The theoretical framework for the research includes authors such as Mary Ann Mahony (2001, 2007, 2018) to discuss slavery; Rogério Haesbaert (2021) to comprehend land and territory; Luís Bueno (2006) to debate the historical context of Jorge Amado; Aníbal Quijano (2005) to contemplate coloniality, among others.